VOLATILITY, PRICE TRANSMISSION AND VOLATILITY SPILLOVER ANALYSIS OF TOMATO IN MALANG AND KEDIRI REGENCIES - Amylia Rahma Nurbani; Ratya Anindita; Suhartini Suhartini (Socio-Economics/Agribusiness Department, 2016)
Fluctuation on tomatoes’ prices is considered unstable as well as unpredictable due to several obstructions on demands and supply, which are deemed to yield a price volatility. The indefinite and erratic price, in addition, opens a possibility for sellers to manipulate a couple of information related to the price so that consumers will not be transmitted to the price that has been collectively decided by farmers. This research aimed at analyzing the volatility, price transmission, and spillover volatility of tomatoes in Malang and Kediri Regencies, considering both the regencies are the biggest tomato producers within East Java. Furthermore, for data analysis, historical volatility approach was employed to measure the volatility, simple regression of Ordinary Least Square Method to measure the price transmission, and GARCH regression method for spillover volatility measurement. The research, moreover, unveiled that the price volatility, within the context of producers and consumers from the both regencies, increased significantly. In addition, the price transmission also happened to occur between the consumer and the producer prices in Malang Regency as that of in Kediri Regency. Besides, the typical condition also occurred, in terms of spillover volatility, engaging the consumer and the producer prices in both the regencies.